Will sustainability shape the future wine market? - Eugenio Pomarici; Riccardo Vecchio (Wine Economics and Policy)
Technical improvements in the sustainability of wine making will likely proceed thorough a progressive refinement of processing strategies without substantial discontinuities. The new varieties obtained through interspecific crossings represent a new technological paradigm with remarkable effects on cropping conditions. Indeed, vineyards planted with these new varieties require few treatments and result in a dramatic reduction in the pesticide use, production costs and carbon footprint. Wine consumption scholars should closely examine how the media will communicate these varieties to the general public, as we anticipate that this will influence consumers’ perception of risk and, in turn, directly affect the market. Keywords: New varieties, Consumer preferences, Denomination of origin